Personal exposure to nitrogen dioxide and risk of airflow obstruction in asthmatic children with upper respiratory infection. Issue 11 (1st November 2000) - Linaker, C H; Coggon, D; Holgate, S T; Clough, J; Josephs, L; Chauhan, A J; Inskip, H M
Abstract : BACKGROUND: Several studies have linked air pollution by nitrogen dioxide (NO2 ) with increased hospital admissions for asthma in children. Exacerbations of asthma in children are often precipitated by upper respiratory infections. It is therefore possible that NO2 increases the risk of airways obstruction when asthmatic children develop upper respiratory infections. METHODS: To test this hypothesis a sample of 114 asthmatic children aged 7–12 years were followed for a total of up to 13 months. Probable upper respiratory infections were identified by consensus review of daily symptom diaries, and episodes of airways obstruction from serial records of peak expiratory flow (PEF). Personal exposures to NO2 were measured with Palmes tubes that were changed weekly. Generalised estimating equations were used to assess the relative risk (RR) of an asthmatic exacerbation starting within seven days of an upper respiratory infection according to estimated NO2 exposure during the one week period from two days before to four days after the onset of the infection. RESULTS: The children were followed for an average of 34 weeks during which 318 upper respiratory infections and 224 episodes of reduced PEF were diagnosed. PEF episodes were much more likely to occur in the seven days following the onset of an upper respiratory infection than at other times. Estimated exposures to NO2 at the time of infections were generally low (geometric mean 10.6 μg/m 3 ). Compared with exposures of ⩽8 μg/m 3, exposures of >28 μg/m 3 were associated with a RR of 1.9 (95% confidence interval 1.1 to 3.4) for the development of an asthmatic episode within seven days of an infection. CONCLUSIONS: The findings give some support to the hypothesis that NO2 increases the risk of asthmatic exacerbations following respiratory infections, even at relatively low levels of exposure. Further studies in populations with higher exposures would be useful.